Analisis Perlindungan Hukum Bagi Dokter Gigi Praktik Mandiri dalam Pandemi Covid-19 - Erni Susanty Tahir; Puput Mulyono (Jurnal Kesehatan Amanah, 2025)
The transmission of Covid-19 transmission is very fast and causes many medical personnel to die including dentists so that many dentists refuse to take action on patients who have not been vaccinated against Covid-19 and close their independent practice places so that this actually puts dentists in a position as bearers of various obligations by a series of sanctions if dentists do not carry out health services properly and are only concerned with themselves. The purpose of this study is to explain the regulations governing legal protection for independent practice dentists who refuse action on patients who are not vaccinated against Covid-19, explain the efforts of professional organizations and the Cirebon Regency government in preparing regulations to protect independent practice dentists who refuse action on patients who are not vaccinated against Covid-19 and formulate the concept of an ideal regulatory arrangement in protecting independent practice dentists who refuse to take action on patients who are not vaccinated against Covid-19. The research method used is an empirical juridical approach with secondary and primary data collection. The results of further research were analyzed qualitatively. The results of the study show that in fact dentists who refuse to provide treatment to patients who are not vaccinated against Covid-19 are a right that must be fulfilled by statutory regulations. No efforts have been made by Professional Organizations and Regional Governments in preparing regulations to protect independent practicing dentists who refuse to take action on patients who are not vaccinated against Covid-19, and the principle is only to comply with existing regulations from the Central Government. The ideal regulatory concept is behavior that starts with the community itself, because law is a social engineering formed by the community itself. Thus, the whole society and also the state can be subject to the same legal system, namely the balance between positive law and also the concept of living law.